Effect of environment and peeling in the glycoalkaloid concentration of disease-resistant and heat-tolerant potato clones - Munoa, L.P.; Chacaltana, C.; Sosa, P.; Gastelo, M.; Felde, T. zum; Burgos, G. (Elsevier, 2022)
The effect of environment and peeling on the glycoalkaloid concentration of late blight-resistant and heat-tolerant potato clones was determined by ultraperformance liquid chromatography (UPLC). Significant variation due to clone, environment and clone x environment (G x E) interaction was found. Total glycoalkaloids (TGA) concentration in raw unpeeled tubers ranged from 1.37 to 33.35 mg / 100 g on a fresh weight basis (FW). The α-chaconine, α-solanine and TGA concentrations of all the late blight-resistant and heat-tolerant clones and varieties evaluated in this study were higher under heat stress conditions. The clones 398098.570, 398192.213 and 398208.219 have less than 10 mg / 100 g FW of glycoalkaloids under heat stress conditions and are recommended for distribution. TGA concentration of clones and varieties was reduced from 5 to 73% with a mean reduction of 33% after peeling. However, under heat stress conditions, clones 398098.203 and 398098.204 presented unsafe levels of TGA even after peeling and have been removed from the list of late blight-resistant and heat-tolerant clones recommended for distribution. Peeling reduced the TGA concentration of clone 393371.58 to a safe level when grown under heat stress conditions.